2017
DOI: 10.7287/peerj.preprints.2638v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Local genes for local bacteria: evidence of allopatry in the genomes of transatlantic Campylobacter populations

Abstract: 35The genetic structure of bacterial populations can be related to geographical locations of 36 isolation. In some species, there is a strong correlation between geographical distance and 37 genetic distance, which can be caused by different evolutionary mechanisms. Patterns of 38 ancient admixture in Helicobacter pylori can be reconstructed in concordance with past 39 human migration, whereas in Mycobacterium tuberculosis it is the lack of recombination that 40 causes allopatric clusters. In Campylobacter, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…jejuni isolated from chicken, ruminant, environmental water and wild birds from different countries and published in previous studies (Fig. 4 ) 85 – 88 . This gave a total of 859 C .…”
Section: Methodsmentioning
confidence: 76%
“…jejuni isolated from chicken, ruminant, environmental water and wild birds from different countries and published in previous studies (Fig. 4 ) 85 – 88 . This gave a total of 859 C .…”
Section: Methodsmentioning
confidence: 76%
“…Furthermore, C. coli from clinical and animal samples have displayed resistance to macrolides including erythromycin and the aminoglycoside streptomycin (Food and Authority, ). More worryingly, there is an apparent trend towards multidrug resistance (MDR), particularly among C. coli that regularly harbour different AMR genes simultaneously within the genome of a single isolate (Luangtongkum et al ., ; Pascoe et al ., ; Food and Authority, ).…”
Section: Introductionmentioning
confidence: 99%
“…Technical advances in high-throughput genome sequencing and analysis methods continue to improve understanding of C. jejuni from bottom-up studies that test the function of specific genes or operons, often with insertion or deletion mutants [55, 97], to top-down comparative genomic approaches in which isolates are clustered by phenotype and associated genomic variations are identified in large genome collections [50, 64, 100]. Early genome typing using DNA microarrays hinted at the level of diversity among C.…”
Section: Resultsmentioning
confidence: 99%
“…Early genome typing using DNA microarrays hinted at the level of diversity among C. jejuni isolates [27, 101], and comparisons of large isolate genome collections are now linking strain variation to differences in ecology [65, 102–105], epidemiology and evolution [63, 100, 106–110]. Advances in sequencing technology are helping us to study genome variation in greater depth, and long read sequencing of isolate 2 identified large inversions (>90 000 bp) compared to the original finished genome (Table S1).…”
Section: Resultsmentioning
confidence: 99%